2015
DOI: 10.1371/journal.pone.0118730
|View full text |Cite
|
Sign up to set email alerts
|

Volume Regulation and Renal Function at High Altitude across Gender

Abstract: AimsWe investigated changes in volume regulating hormones and renal function at high altitudes and across gender.MethodologyIncluded in this study were 28 subjects (n = 20 males; n = 8 females. ages: 19 – 65 yrs), who ascended to a height of 3440m (HA1), on the 3rd day and to 5050m (HA2), on the 14th day. Plasma and urinary creatinine and urinary osmolality as well as plasma levels of plasma renin activity (PRA), Aldosterone, antidiuretic hormone (ADH), and atrial natriuretic peptide (ANP) were measured. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 31 publications
(36 reference statements)
1
35
0
Order By: Relevance
“…The increase in ventilatory response and diuresis during acute high altitude exposure appears to be an obligatory early phase of acclimatization to altitude. Moreover, volume regulation is considered one of the key physiological process central for both high altitude acclimatization, adaptation and mal-adaptation [ 5 ]. The strong positive correlation between the progression of kidney injury and decline in oxygen tension (pO 2 ) suggests the existence of causal involvement between hypoxemia and renal dysfunction [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in ventilatory response and diuresis during acute high altitude exposure appears to be an obligatory early phase of acclimatization to altitude. Moreover, volume regulation is considered one of the key physiological process central for both high altitude acclimatization, adaptation and mal-adaptation [ 5 ]. The strong positive correlation between the progression of kidney injury and decline in oxygen tension (pO 2 ) suggests the existence of causal involvement between hypoxemia and renal dysfunction [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the risk of high altitude-induced kidney dysfunction and its systemic effects are also currently unclear. Except few case reports, there is not enough evidence (human or animal studies) that proves an association between altered kidneys function and increased incidence of high altitude induced systemic complications [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The kidneys have a fundamental role in adaption to regulate body fluids, electrolyte and acid-base homeostasis during acclimatization to high altitude and in mountain sickness syndromes. Kidneys also respond to hypoxic diuresis and natriuresis through inhibition of renal tubular sodium reabsorption, in addition to erythropoietin production (Haditsch et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen articles were included in the review (shown in Table 1 ). Renal tissue adaptation to altitude-induced hypoxia was either investigated in a rat model (Thron et al, 1998 ; Al-Hashem et al, 2012 or human model Lewis et al, 1997 ; Bestle et al, 2002 ; Cumbo et al, 2002 , 2015 ; Ge et al, 2002 ; Jefferson et al, 2002 ; Singh et al, 2003 ; Loeppky et al, 2005 ; Haditsch et al, 2007 , 2015 ; Pichler et al, 2008 ; Zouboules et al, 2018 ). Duration of exposure to high altitude ranged from 8 h (Loeppky et al, 2005 ) to 90 d (Al-Hashem et al, 2012 ), with an altitude up to 5,800 m above sea level (Singh et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%